Auditoría de gestión y su incidencia en la eficiencia y eficacia empresarial de agrocomercio Cox Yoong, cantón El Empalme, año 2013 - Manzaba Párraga, Ingrid Lisbeth (2016)
This research is focused on the business operation process of the company agribusiness COX Yoong, during the period 2013, which aims to analyze the operational perspective of the entity based on compliance with policies, laws and regulations in every area of the same order to carry out an audit and its impact on business efficiency and effectiveness of the company. The methodology of research methods such as inductive, deductive and analytical were used, these methods are considered the most appropriate as to run an audit. As for the techniques was used to interview, so it is a technique for obtaining information directly. The execution of this work included evaluation of internal control through the questionnaire, the findings in the absence of organic status, operational manual were found and include the lack of an organizational structure that allows leading entity correctly. As a major part of this research, conclusions and recommendations were made all of which must be analyzed and simultaneously executed by the administration Agrocomercio Cox Yoong.